Keanekaragaman tanaman dan potensi kebermanfaatannya di Wisata Lembah Alam Jepara - Ariestya, Zulfina; Wijayanti, Erna (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2024)
Wisata Lembah Alam Jepara is a garden restaurant destination showcasing a variety of interesting plants. This study aims to identify the diversity of plant species that have the potential to be cultivated and utilized by the owners and the surrounding community, as well as to support the conservation of local plants. The methods used in this research are exploratory studies and literature reviews. The results of the study revealed that there are 13 plant species with potential for development. These plants have various benefits, including as ornamental plants, medicinal plants, food sources, dye materials, educational resources, air filters, and pest control for other plants. Knowledge of the potential of these plants is expected to increase awareness and utilization of plants by the community around Wisata Lembah Alam Jepara, as well as to support the conservation of local biodiversity.